Recent trends on electromagnetic environmental effects for aeronautics and space applications - Nikolopoulos, Christos D., 1981- (Advances in mechatronics and mechanical engineering (AMME) book series., 2021)
"This book provides relevant theoretical frameworks and the latest empirical research findings in the area of Electromagnetic Compatibility and Electromagnetic Interference (EMC/EMI) for aerospace industry and will help professionals who want to improve their understanding of the emissions and immunity regarding aerospace design engineering"--